Benign prostate hyperplasia as a potential protective factor against prostate cancer: Insights from a magnetic resonance imaging study of compositional characteristics. Issue 14 (10th August 2021) - Nandalur, Kiran R.; Colvin, Robert; Walker, David; Nandalur, Sirisha R.; Seifman, Brian; Gangwish, David; Hafron, Jason
Abstract: Purpose: The structural relationship between benign prostate hyperplasia (BPH) and prostate cancer (Pca) is controversial. The purpose of our study was to examine the association between quantitative prostate compositional metrics by magnetic resonance imaging (MRI) and Pca. Methods: We identified 405 patients who underwent prostate MRI and biopsy and/or prostatectomy from January 2019 to January 2021 at our institution. Segmentation volumetric methods were used to assess central gland (CG) and peripheral zone (PZ) volume. PZ mean thickness and mean apparent diffusion coefficient (ADC), marker of underlying histologic components, were measured. Multivariable logistic regression was performed with outcomes of ≥Grade Group (GG) 2 Pca and for multifocal disease. Results: On multivariable analysis, higher CG volumes were at lower odds of ≥GG2 disease ( n  = 227) (OR: 0.97, 95% CI 0.96–0.98, p  < 0.0001), taking into account PZ volume ( p  = 0.18) and thickness ( p  = 0.70). For every one cc increase in CG volume, there was an approximately 3% decrease in odds of ≥GG2 disease. Similar findings were noted for multifocal disease ( n  = 180) (OR: 0.97, 95% CI 0.96–0.98, p  < 0.0001). Notably, ADC of the normal PZ was not significantly associated with CG volume ( p  = 0.21) nor a predictor of disease ( p  = 0.49). Conclusions: Increasing central gland volume, driven by BPH, is associated with lower odds of significant Pca, including multifocal disease, while PZ anatomic and histologic surrogate changes were noncontributory. Findings support BPH impediment of global tumor growth predicted by theoretical mechanobiological model. This potential stabilizing factor should be further studied for risk stratification and in consideration for BPH therapy.